Complex formation of APP with GABAB receptors links axonal trafficking to amyloidogenic processing - Dinamarca, Margarita C; Raveh, Adi; Schneider, Andy; Fritzius, Thorsten; Früh, Simon; Rem, Pascal D; Stawarski, Michal; Lalanne, Txomin; Turecek, Rostislav; Choo, Myeongjeong; Besseyrias, Valérie; Bildl, Wolfgang; et al. (Nature communications, 2019)
GABAB receptors (GBRs) are key regulators of synaptic release but little is known about trafficking mechanisms that control their presynaptic abundance. We now show that sequence-related epitopes in APP, AJAP-1 and PIANP bind with nanomolar affinities to the N-terminal sushi-domain of presynaptic GBRs. Of the three interacting proteins, selectively the genetic loss of APP impaired GBR-mediated presynaptic inhibition and axonal GBR expression. Proteomic and functional analyses revealed that APP associates with JIP and calsyntenin proteins that link the APP/GBR complex in cargo vesicles to the axonal trafficking motor. Complex formation with GBRs stabilizes APP at the cell surface and reduces proteolysis of APP to Aβ, a component of senile plaques in Alzheimer's disease patients. Thus, APP/GBR complex formation links presynaptic GBR trafficking to Aβ formation. Our findings support that dysfunctional axonal trafficking and reduced GBR expression in Alzheimer's disease increases Aβ formation.
Keywords: Protein Binding; Protein Stability; Cell Adhesion Molecules; stabilita proteinů; kineziny; HEK293 buňky; Synapses; proteiny vázající GTP; dendrity; Epitopes; molekuly buněčné adheze; signální transdukce; synapse; proteiny nervové tkáně; Amino Acid Sequence; receptory GABA-B; axonální transport; epitopy; HEK293 Cells; amyloidní beta-protein; Kinesins; Signal Transduction; GTP-Binding Proteins; proteomika; axony; vazba proteinů; Cell Membrane; Animals; lidé; Amyloid beta-Peptides; Humans; zvířata; buněčná membrána; amyloid; myši inbrední C57BL; sekvence aminokyselin; Mice, Inbred C57BL; Receptors, GABA-B; Dendrites; Axons; Proteomics; Axonal Transport; Amyloid; Nerve Tissue Proteins